A Case Study in the Implementation of a Human-Centric Higher Education Cybersecurity Program - John W. Coffey; Melanie Haveard; Geissler Golding (Journal of Cybersecurity Education, Research & Practice)
This article contains a description of the implementation of a comprehensive cyber security program at a regional comprehensive university. The program was designed to create an effective cyber security management infrastructure and to train end users and other categories of security management personnel in data protection and cyber security. This work addresses the impetus for the program, the rather extensive planning and development that went into the program, its implementation, and insights gleaned from the experience. The paper concludes with a summary of the strengths and weaknesses of the initiative.